Effective Factors on Oral Health Behaviors of 12-year-old Children in Cities and Villages of Iran: a Path Analysis - Maryam Rad; Arash Shahravan; Ali Akbar Haghdoost (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: Oral and general health status depends on several factors such as the individual's personal attributes, behaviors, and perceptions. Purpose: This study aimed to evaluate the factors affecting the oral health-related behaviors in 12-year-old children. Materials and Method: This cross-sectional study was based on the data obtained from 1554 students being 12 years old and from five provinces in Iran. The data were collected with a culturally adapted questionnaire about the students' demographic characteristics, knowledge, attitudes, and practice (KAP). Path analysis was conducted to evaluate the effect of these factors on oral health-related behaviors in urban and rural areas. Results: Based on the findings, 61.1% of the samples resided in urban and 38.9% in rural areas. The mean scores were relatively good for knowledge (74.1±21.1%) and attitudes (72.6±21.1%), but unsatisfactory for oral health practice (51.8±12%). Having measured the correlation between the independent variables and oral health-related behaviors, the province of residence and the parents' education and job had the most significant correlations. Behavioral biases were seen in all dimensions of practice such as brushing habits, dental visits, and diet. In urban areas, 30% and in rural areas 49% of oral health behaviors were directly related to knowledge and attitudes. All of the calculated effects exhibited significant differences from zero (p< 0.0001). Conclusion: Path analysis identified some direct and indirect factors influencing the children's oral health-related behaviors. Factors included in this model could only justify a part of oral health behaviors. Thus, other educational models should be considered based on the psychology or social learning theories.